Visual Evoked Potentials in Phenylketonuria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Visual evoked potentials (VEPs) were studied in 36 patients with phenylketonuria, and compared with MRI findings, dietary state, and IQ at the Institute of Neurology, Queen Square, and the Institute of Child Health, Great Ormond Street Hospital, London, UK.